2019
DOI: 10.1016/j.arabjc.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of anthra[1,9-cd]pyrazol-6(2H)-one scaffold derivatives as potential anticancer agents

Abstract: Severalanthrapyrazolone derivatives derived from 7-chloroanthra [1,9-cd]pyrazol-6(2H)-one and 7-chloro-2-(2-hydroxyethyl)anthra [1,9-cd] pyrazol-6(2H)-one have been prepared by addition or substitution nucleophylic reactions and further transformed into extended tetracyclic systems and fused to different nitrogenheterocyclic rings into the pharmacophore structure moiety. The compounds synthesized were evaluated for their cytotoxic activity and telomerase activity in prostate cancer cell line by SRB assay and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Column chromatography followed by treatment with 1N HCl in methanol was used to obtain water-soluble hydrochloride salts of 2a-c. The assigned structures of 2a-c were confirmed by 1 H and 13 C NMR; the purity of the final samples was >95% (Figure S1 in Supplementary Materials).…”
Section: Synthesis Of Heteroarene-fused Anthraquinonesmentioning
confidence: 82%
See 2 more Smart Citations
“…Column chromatography followed by treatment with 1N HCl in methanol was used to obtain water-soluble hydrochloride salts of 2a-c. The assigned structures of 2a-c were confirmed by 1 H and 13 C NMR; the purity of the final samples was >95% (Figure S1 in Supplementary Materials).…”
Section: Synthesis Of Heteroarene-fused Anthraquinonesmentioning
confidence: 82%
“…Melting points were determined using a Buchi SMP-20 apparatus and are given uncorrected. 1 H and 13 C NMR spectra were recorded on a Varian Mercury 400 Plus instrument operated at 400 MHz and 100 MHz, respectively. Chemical shifts were measured in DMSO-d 6 using tetramethylsilane as an internal standard.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is a group of various diseases, i.e., lung cancer, cervical cancer, prostate cancer, and breast cancer, and all of them are characterized by an abnormal control of cell growth [19]. Despite many clinically successful anticancer drugs have been developed either natural products or synthetic derivatives of naturally occurring lead compounds, there are still limitations in the treatment of cancer including the effectiveness of drugs and serious side effects [20]. Hence, many pyrazole-based compounds have been synthesized and screened by scientists.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we chose 32 substitutions of anthra[1,9-cd]pyrazol-6(2H)-one for which their anticancer activities are reported in the literature by Chen et al [24]. On the other side and for the 2DQSAR study, the reported values of IC50 have been converted into PIC50 by taking negative logarithm (PIC50 = log 10 IC50) and subsequently used as the dependent variable for the 3D-QSAR model development.…”
Section: Experimental Datamentioning
confidence: 99%